L'impact de la tempête "Martin" sur le couvert forestier en Auvergne. Origine des chablis et logique de reconstitution - Fabien Jubertie (Physio-Géo)
The December 27th of 1999 storm left lasting marks on the Auvergne forest cover. Therefore, it seems interesting today not only to know the reasons which explain the localization and extent of the damages but to tackle the reconstitutions problem too.The oceanic low pressure system responsible for the stormy gusts (158 km/h recorded at Clermont-Aulnat!) is out of the ordinary. It was remarkable because of its small size, its mobility and above all by the fact that it reached its maximum intensity while penetrating inland. In a general manner, the winds reached, in the Auvergne, values almost comparable to those which had been recorded during the South storm of November 1982, a reference event for the Massif Central. Heavy rains associated with these violent winds were recorded. Moreover, as the soils were widely waterlogged, the impact of the storm on the forests was more effective.The unequal repartition of the windfallen woods appears clearly on visualization of the departmental damage maps established by the "Inventaire Forestier National" (NationalForestry Assessment) as well as on local scale carried out by myself in a pilot forest of the Haute-Loire. The interpretation of these maps enables us to show main interactions between meteorological and orographical factors. They demonstrate the excessive density of conifers that were planted mainly after the Second World War.As a result, the damages importance, partly linked to bad forestry management, led the forest managers to put into question the practices that were used until now. A new forest reconstitutions strategy seems to develop today. Natural regenerations are carried out for the smaller plots thus contributing to species diversification (and the coming back of broadleaved trees). Artificial reforestations consist now in planting a lower density of trees per hectare. All these measures must enable a decrease in vulnerability of these areas facing the wind.